(untitled) (Research, Society and Development, 2021)
This article aims to analyze how Multiprofessional Residency in Family Health contributes to the Permanent Health Education of the Family Health Strategy team. For this, we used qualitative research, descriptive exploratory type as methodological procedures. The study takes place with workers from the multidisciplinary team of the São João Family Health Basic Unit, located in the city of Rio Grande/RS. Data collection was performed by semi-structured interview, recorded, through the focus group technique and, for qualitative analysis, the method used was based on content analysis. The results were presented in three categories: 1) Contributions of Multiprofessional Residency in Family Health through Permanent Health Education 2) Changes in the work process of the team 3) The importance and ways of addressing Permanent Health Education. It is evident that the multiprofessional resident is an important catalyst of stimuli, because it adds changes with a view to training and personal, professional and team development, through the permanent health education tool. It was concluded that when the Multiprofessional Residency in Family Health uses education as a pedagogical foundation, it reorganizes the work process, through the updating of emerging themes, stimulates the reflection and discussion of cases with a multidisciplinary view and also establishes the space of Permanent Education in Health, which will then qualify the integrality of care, the reception, the expanded clinic and the humanization of care.